Creative Economy of Batik: Product Design, Service Quality, Pricing, and Customer Satisfaction - Sanggarwati, Diah Ayu; Hayati, Cucu (Global Economic, Social, and Development Review, 2025)
The batik creative industry is important and vital to Indonesia's cultural economy, but it faces challenges from digital competition and changing consumer behavior. This study examines how product design, service quality, and price affect customer satisfaction when purchasing bold batik online. It builds on earlier research that studied these factors one at a time. The study used a quantitative approach to collect data from 300 people who purchased batik through digital platforms, and employed the SEM-PLS method for analysis. The results show that all three factors—product design, service quality, and price—positively and significantly influence customer satisfaction. Among them, product design has the biggest and most significant impact, showing how important design innovation is for the most significant impact, underscoring the importance of design innovation in keeping the batik industry connected to cultural identity. Digital service quality and fair pricing also help shape the customer experience and satisfaction. The study suggests that small and medium businesses should focus on improving design through technology, boosting digital service quality, and adopting pricing strategies that add value. From a policy standpoint, there is a need for digital training, authentic product certification, and financial support to help these businesses remain competitive and sustainable in the long run.